Antibacterial activity of Piper nigrum, Coriandrum sativum, Trigonella foenum-graecum and Ferula narthex - S Mohan, A K Valsa, Dhanya Vijayan, K Deepamol, R Manjula, (Journal of Spices and Aromatic Crops, 2003)
The antibacterial activity of water and acetone extracts of black pepper, coriander, fenugreek and asafoetida was tested against six clinically important bacteria namely Escherichia coli, Klebsiella sp., Staphylococcus aureus, Bacillus sp., Salmonella typhi and Salmonella paratyphi A, by disc diffusion method, in the lawn culture of the organisms in nutrient agar. E. coli was found to be susceptible to all the extracts, except the water extract of black pepper. The growth of S. fyphi and S. pomtyphi A was also inhibited by various extracts. Thus our resul ts support the evidence that spices, not only provide flavour to food, but also check the growth of some of the undesirable bacteria.